Totally Laparoscopic Right Hepatectomy for Living Donor Liver Transplantation: Analysis of a Preliminary Experience on 5 Consecutive Cases. Issue 3 (March 2017) - Rotellar, Fernando; Pardo, Fernando; Benito, Alberto; Zozaya, Gabriel; Martí-Cruchaga, Pablo; Hidalgo, Francisco; Lopez, Luis; Iñarrairaegui, Mercedes; Sangro, Bruno; Herrero, Ignacio
Abstract : Background: The pure laparoscopic approach in right hepatectomy (LRH) for living donor liver transplantation (LDLT) is a controversial issue. Some authors have reported the procedure to be feasible but surgical outcomes and impact on short and long-term morbidity rates are yet to be determined. The aim of this study is to present the results of a preliminary 5 consecutive cases series of LRH for LDLT and to compare it with a successive cohort of open right hepatectomies (ORH) for LDLT. Methods: From May 2013 to October 2015, 5 consecutive donors underwent LRH for LDLT in our center. The previous last 10 ORH for LDLT were selected for comparison. Special care was taken to include all adverse events. Each patient's complications were graded with the Clavien-Dindo Classification and scored with the Comprehensive Complication Index. Results: All 5 consecutive donors completed a pure laparoscopic procedure. All allografts (open and laparoscopically procured) were successfully transplanted with no primary graft failures. Only 2 Clavien-Dindo Grade-I complications occurred in the LRH donors, while ORH donors had 10 Grade I, 2 Grade II and 1 Grade IIIa complications in the short term (<3 months). In the long term (6–12 months follow-up), LRH donors had a significant lower incidence of complications (Comprehensive Complication Index: 1.74; SD, 3891 vs 15.2 SD; 8.618; P = 0.006). Conclusions: In our experience, LRH for LDLT is a feasible procedure. Further comparative series may support our preliminary findings of reduced incidence and severity of complications as compared with the open approach. Abstract : The authors report their first series of laproscopic right lobe procurements. Going beyond single case reports experience is now being accumulated around the world to indicate that functional grafts can be recovered safely using highly successful techniques in carefully selected patients. Supplemental digital content is available in the text.